Zheng He Hanghai Tu (Nautical Chart of Zheng He) : a reappraisal - Ku, Boon Dar; Goh, Sang Seong (Penerbit Universiti Kebangsaan Malaysia, 2021)
This article attempts to analysis the manuscript of Zheng He Hanghai Tu (Nautical Chart of Zheng He). The sailing chart, comprising a set of navigational notes written by Admiral Zheng He, was published in the military pamphlet of the Ming dynasty, Wubei Zhi. The study is divided into three parts. The first part examines the history of the development of Zheng He Hanghai Tu, the second part explores the essence of the contents of this work and the third part discusses its important role during the Ming dynasty, which attempted to understand the geography of the world. This study used qualitative methods and referred to the map related to East African locations, revealing that most of the entries in the country map and the old-generation population register have not been analysed. Using Zheng He Hanghai Tu, this article also divided the zones of the South China Sea archipelago into Shitang (Paracel Island), Wansheng Shitangyu (Macclesfield Bank) and Shixing Shitang (Spratly Islands) to explain that the Ming dynasty progressively understood the geography of Southeast Asia, Persia, Arab and Africa. This article reveals insights into how, through his long voyages, Zheng He gained a new understanding of these places in particular and of world geography in general.